COVID-19 Pneumonia Complicated by Acute Pulmonary Embolism - Ahmed, M; Sultana, M (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Abstract not available J Bangladesh Coll Phys Surg 2020; 38(0): 82-83